Image Compression Using Proposed Enhanced Run Length Encoding Algorithm - Husseen, A. H.; Mahmud, S. Sh.; Mohammed, R. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we will present proposed enhance process of image compression by using RLE algorithm. This proposed yield to decrease the size of compressing image, but the original method used primarily for compressing a binary images [1].Which will yield increasing the size of an original image mostly when used for color images. The test of an enhanced algorithm is performed on sample consists of ten BMP 24-bit true color images, building an application by using visual basic 6.0 to show the size after and before compression process and computing the compression ratio for RLE and for the enhanced RLE algorithm